Electrolitos en pacientes hospitalizados con COVID-19 en el Hospital Nuestra Señora de las Mercedes de Paita, Perú. 2020 - 2021 - Cavero Avalos, Marvin Lenin (2023)
The objective of this study was to determine the frequency of normal and abnormal electrolyte values in patients hospitalized for COVID-19 at the Hospital Nuestra Señora de las Mercedes in Paita, Peru, between March and May 2021. The records of the epidemiology and digital medical records unit of hospitalized patients diagnosed with COVID-19, from where age and sex data were collected, to then access the laboratory records from which the blood electrolyte values were obtained, both of sodium, potassium and chloride, obtained by the potentiometry method in arterial blood, considering as normal values: sodium ≥135 and ≤144 mEq/L; potassium ≥3.5 and ≤5.49 mEq/L; chloride ≥96 and ≤110 mEq/L. The data was processed using descriptive statistics in Excel tables. Results were obtained from 80 patients of both sexes with an average age of 57.2 years where the frequency of normal sodium values was 75%, hyponatremia 15% and hypernatremia 10%; the frequency of normal potassium values was 73%, hypokalemia 26%, and hyperkalemia 1%; the frequency of normal chloride values was 81%, hyperchloremia 15%, and hypochloremia 4%. Therefore, in the present study it was observed that the most frequent electrolyte alterations found in patients hospitalized for COVID-19 at the Hospital Nuestra Señora de las Mercedes de Paita, between March and May 2021; They are hypokalemia 26%, hyponatremia 15% and hyperchloremia 15%.